(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 1998)
The archipelago of Chiloé holds an exceptional interest for researchers and scholars of various folkloric manifestations, which provide insight into a way of personal and collective existence. They manifest an art of integral life, whether through their religious festivities, customs, narratives, etc., which have managed to endure despite the changes brought about by processes of urbanization, industrialization, and technological advancements. The reviewed book, focused on the realm of romancero, investigates artistic creations, mainly romances from the Spanish tradition, as a result of the presence and influence of the conquistadors.